The Effects of High Performance Work Systems on International Governmental Organizations: A Study of the United Nations Relief and Works Agency for Palestine Refugees in the Near East Headquarters - El-Ghalayini, Yousif (Université d'Ottawa / University of Ottawa, 2014)
In the last three decades, a growing body of research has suggested that using a mix or system of human resources management (HRM) practices can lead to superior organizational performance. These practices (such as selective recruitment and hiring procedures, performance-based compensation systems, employee participation, and training and development) have been referred to as high performance work systems (HPWS) and originated from the study of strategic human resource management (SHRM), where researchers have examined the impact of these systems on organizational performance outcomes. The relationship between HRM and organizational performance has received increasing interest from scholars and practitioners in the field of public administration. Scholars strive to identify the effects of HRM practices on organizational performance based on the notion that these practices will lead to enhanced attitudinal outcomes, such as organizational commitment, job satisfaction, and motivation, which will have positive impacts on organizational performance. This study contributes to further our understanding of the impact of management on performance in public organizations through empirical evidence drawn from theories of HRM. The growing interest among scholars in understanding the effects of management on performance presumes that the adoption of best practices will lead to improvements in organizational performance. The purpose of this mixed-methods study is to examine the effects of HPWS practices on individual worker attitudes in international governmental organizations (IGOs) by reporting the results of a staff survey and follow-up interviews conducted on a cross-section of the United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) employees. The UNRWA is an international relief and human development Agency with a quasi-governmental role, delivering essential public services to over five million registered Palestinian refugees. UNRWA services include education, healthcare, social services, and emergency aid. In 2006, the UNRWA began a comprehensive reform program to strengthen its management capacity. Accordingly, one of the main achievements of the reform process is the deployment of new HRM systems that included recruitment strategies, performance appraisals, training and development, and compensation and rewards systems. The underlying message of the reform process has been adopting HPWS practices, which is the object of this study. Since the 1990s, the UNRWA has become increasingly interested in policy analysis and organizational research. Especially because of recent changes in the Agency’s management style, the UNRWA has become more focused on integrating knowledge and management research into its work. Therefore, when the researcher sought permission to examine the effects of the newly adopted HPWS practices on employee attitudes, the staff and upper management were very collaborative and co-operative. Surveys and interviews were conducted with program administrators, operations directors, and field staff, representing employees from different countries with varying lengths of service as well as an extensive range of levels of education and professional backgrounds. A total of 505 questionnaires were distributed in seven service departments and a total of 234 usable responses were obtained. In addition to questionnaires, a total of 10 face-to-face interviews were conducted to explore the data obtained from questionnaires and to understand further the implications of applying HPWS practices in an IGO context. Statistical analysis of the survey data and interviews provided a representation of the effects of four bundles of HPWS adopted by the organization (independent variables), on four worker attitude measures (dependent variables). The four independent variables are the HPWS practices that are the most common and most accepted in the HRM literature: staffing and recruitment, compensation and rewards, performance appraisal, and training and development. The four dependent variables are employee commitment, job satisfaction, motivation, and intention to quit. Preliminary statistical analysis consisted of descriptive statistics for all study variables, as well as Cronbach’s alpha for measuring the internal consistency reliability coefficients for all the survey subscales to examine its internal consistency. Four research hypotheses were tested using multiple regression analyses and Pearson correlation coefficients in an attempt to estimate the net effect of each of the independent variables and understand the relationship between study variables. The bivariate relationships between the dependent and independent variables have shown that the relationships are in the anticipated directions. One of the main conclusions regarding the effects of specific HPWS practices in an IGO context is that some practices, such as training and development, outperform other practices, such as staffing and recruitment. These findings are consistent with previous research on multinational corporations operating in different national contexts, and other studies comparing the effects of HPWS in different industries. The results also indicated that HPWS practices have synergistic and complementary effects on each of the employee attitudes that exceed their individual effects. Therefore, in order to expand our understanding of the effects of HPWS on organizational performance, different variables need to be considered such as national context, industry, and other organizational factors may moderate the HRM–performance relationship. The findings of this study support previous studies in this stream of research. The qualitative data were used to verify quantitative data and provide insights that were difficult to gain from surveys alone. The qualitative data indicated that more effective implementation and administration of HPWS practices would lead to better employee outcomes. In other words, the newly announced austerity measures negatively influence perceptions towards the newly implemented HPWS, which may also have influenced employee attitude outcomes.
Keywords: High Performance Work Systems; International Organizations